Addressing implications of culturally empowering pedagogical frameworks: The influence on language, literacy and learning for Mexican Americans and Native Hawaiians. (31st December 2019) - Almaguer, Isela
ABSTRACT: In this study, I emphasize the need to magnify the voices of English language learners through authentic language and literacy learning using a multifaceted culturally relevant and responsive teaching and learning framework with strong social justice underpinnings. Specifically, through the lens of the sociocultural theory to better recognize, acknowledge and understand the influence of culturally relevant learning. Culture plays a crucial role in forming identity and agency so it is important to rethink the effect of culturally relevant pedagogy by linking principles of learning to the cultural realities of children, families, and communities on literacy. English language learners require inclusive pedagogical practices that actively engage them in learning experiences while developing self-efficacy through varied opportunities for academic and linguistic proficiency development to further catapult them as global scholars. As such, parallels exist in literacy development across diverse people and diverse cultures, specifically the Mexican American culture and the Native Hawaiian culture.